2009
DOI: 10.1038/sj.bjc.6605370
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bacterial inflammation induces prostatic intraepithelial neoplasia in mouse prostate

Abstract: BACKGROUND: Although the aetiology of prostate cancer remains unknown, we hypothesised that chronic bacterial insult has a major role in prostate carcinogenesis. METHODS: Male C3H/HeOuJ mice, infected with phosphate-buffered saline or Escherichia coli bacteria, were killed at 5 days, or at 12 or 26 weeks. Harvested prostate tissues were evaluated for inflammatory responses and immunostained for neoplastic transformation markers. RESULTS: All infected mice developed bacterial prostatitis. Control mice had no pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 53 publications
(53 reference statements)
0
51
0
Order By: Relevance
“…For example, expression of certain chemokines is a predictor of biochemical disease recurrence in human prostate cancer (Blum et al 2008). Moreover, administration of the potent heterocyclic amine PhIP (2-amino-1-methyl-6-phenyl-imidazo[4,5-b]pyridine), results in chronic inflammation and promotes prostatic hyperplasia and PIN in rodents (Borowsky et al 2006;Elkahwaji et al 2007;Nakai et al 2007;Elkahwaji et al 2009;Khalili et al 2010). One of the most well-studied genes involved in protection against carcinogens such as PhIP is GSTP1, which encodes a member of the glutathione S-transferase family that is responsible for detoxification of reactive species, and is epigenetically silenced in a majority of prostate cancers by DNA methylation (Nakayama et al 2004).…”
Section: Inflammationmentioning
confidence: 99%
“…For example, expression of certain chemokines is a predictor of biochemical disease recurrence in human prostate cancer (Blum et al 2008). Moreover, administration of the potent heterocyclic amine PhIP (2-amino-1-methyl-6-phenyl-imidazo[4,5-b]pyridine), results in chronic inflammation and promotes prostatic hyperplasia and PIN in rodents (Borowsky et al 2006;Elkahwaji et al 2007;Nakai et al 2007;Elkahwaji et al 2009;Khalili et al 2010). One of the most well-studied genes involved in protection against carcinogens such as PhIP is GSTP1, which encodes a member of the glutathione S-transferase family that is responsible for detoxification of reactive species, and is epigenetically silenced in a majority of prostate cancers by DNA methylation (Nakayama et al 2004).…”
Section: Inflammationmentioning
confidence: 99%
“…Hence, future investigations by crossing these POEAT-3 mice with transgenic mouse models of PCs should help to shed the light on the molecular events involved in the prostatitis and their potential implications in PC development. In this regard, it has been reported that the induction of chronic bacterial prostatitis in C3H/HeOuJ mice by performing an infection with Escherichia coli (E. coli) bacteria led to intense inflammatory infiltrates in the stroma, genotoxic stress and focal atypical hyperplasia in prostatic epithelium [32] . These molecular events were associated with a loss of the expression levels of AR, glutathione-S-transferase, p27 Kip1 and PTEN tumor suppressor proteins as compared to control mice [32] .…”
Section: Inflammation and Pcmentioning
confidence: 99%
“…In this regard, it has been reported that the induction of chronic bacterial prostatitis in C3H/HeOuJ mice by performing an infection with Escherichia coli (E. coli) bacteria led to intense inflammatory infiltrates in the stroma, genotoxic stress and focal atypical hyperplasia in prostatic epithelium [32] . These molecular events were associated with a loss of the expression levels of AR, glutathione-S-transferase, p27 Kip1 and PTEN tumor suppressor proteins as compared to control mice [32] . In the same way, the induction of bacterial prostatitis in C3H/HeOuJ mice by intraurethral inoculation of E. coli has also been associated with a marked decrease of the expression level of Nkx3.1 tumor suppressor protein in infected prostate lobes and development of chronic inflammatory response within 14 d postinoculation [33] .…”
Section: Inflammation and Pcmentioning
confidence: 99%
“…Propionibacterium acnes and Escherichia coli infections of benign prostate cells induce significant changes in cell proliferation rates (122)(123)(124). However, to our knowledge, no studies have assessed how a chronic infection of malignant but otherwise androgensensitive prostate cells would affect disease course.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Recently, inflammation has been proposed as a contributing factor to both prostate cancer initiation and progression (99,100), and it has been demonstrated that P. acnes and uropathogenic E. coli infections have been shown to strongly elicit inflammatory responses and enhance prostate cell proliferation (122)(123)(124) Together these results suggest that HHV-8 promotes an androgen-independent phenotype that does not require activation of and is potentially independent of the AR signaling pathway. Figure 6).…”
Section: Real-time Quantitative Reverse Transcription Pcr (Qrt-pcr) mentioning
confidence: 99%